Pemanfaatan Pestisida Nabati dari Bawang Putih untuk Pertanian di Desa Ciherang - Fairuz, Muhammad; Ridayanti, Hilda; Amirullah, Abdul Aziz; Khairunnisa, Salma Putri; Triesnabayu, Muhammad; Ula, Nahdiyatul; Wachdijono, Wachdijono (Universitas Methodist Indonesia, 2024)
The Community Service Program (KKN) in Ciherang Village aims to introduce and train farmers in making plant-based pesticides from garlic. The use of plant-based pesticides was chosen because it is environmentally friendly and a safer alternative to chemical pesticides, which are known to have negative impacts on human health, plants, and the environment. In this training, farmers are taught how to produce pesticides independently with easily obtained natural ingredients, such as garlic, oil, and liquid detergent. In addition, they are also provided with information about the importance of maintaining the balance of the agricultural ecosystem. The results of this activity show an increase in farmers' awareness of the dangers of using chemical pesticides and a greater interest in switching to using plant-based pesticides. The application of plant-based pesticides has been shown to have positive impacts, such as improving soil quality, reducing pest attacks, and increasing crop yields. It is hoped that this activity can contribute to creating more sustainable agriculture in Ciherang Village.